ബലികുടീരങ്ങളുടെ ഓർമ്മപുസ്തകം - ചന്ദ്രശേഖരൻ, എം ആർ (Green books, 2015)
A memoir that movingly speaks of an earlier age such as the founding of the Communist Party, its work shrouded in secrecy, life in hiding and so on. The Ranadive Thesis, Telangana model that shattered the ease of the comrades. Many become living corpses. At one time, secret meetings in hideaways and brutal beatings by police were regular occurrences. The life of MRC also passes through the history of the communist party in central Kerala. The writer looks back at an unusual time not generally shared by many people, juxtaposing his own life with the work of the organization.